PENGARUH LATIHAN JUMP, SQUAT PUSH-UP DRILL TERHADAP WAKTU REAKSI PADA TIM VOLI PUTRA SMP NEGERI 15 PEKANBARU - suryadi suryadi; Ramadi Ramadi; Ardiah Juita (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2014)
Absract Issues raised in this study is the effect of jump exercise, squats, push-ups against the reaction time drill team SMP Negeri 15 Pekanbaru volleyball. This study aims to determine the effect of jump exercise, squats, push-up drill against reaction time 15 Junior High School volleyball team Pekanbaru. This study is experimental. This research was conducted at the Junior High School 15 Pekanbaru. The study sample as many as 12 people. Data were collected through the initial and final tests with whole-body reaction time reaction. Data were analyzed comparatively, then further testing of research hypotheses that have been proposed, as the issue is: there are significant jump exercises, squats, push-up drill against reaction time 15 Pekanbaru junior volleyball team. Based on t test analysis produces tcount 3,285 and ttable 1,796. Means tcount> ttable. It can be concluded that Ho rejected and H1 is accepted. It was concluded that a significant difference between the exercise jump, squat, push-up drill (X) against reaction time (Y) at the Junior High School volleyball team 15 Pekanbaru.Keywords: jump,squat,push-up drill, reaction time.